Analisa Perbandingan Algoritma HuffmanDengan Rice Code Dalam Kompresi File Video - Melisa Melisa; Nelly Astuti Hasibuan; Ilhamsyah Ilhamsyah (STMIK Budi Darma, 2022)
With the development and advancement of technology, it is something that we should be grateful for, but there are many things that must be considered, one of which is the full storage memory, and also the slow file transfer process so that it takes quite a long time. Data compression (data utilization) is a technique to reduce the amount of data size (compression result) from the original data. To solve this problem, it is recommended to compress video files with the appropriate algorithm in order to get optimal results. The analysis is carried out in comparing the process of how the Huffman algorithm works and the Rice Code algorithm using the exponential method. To compress video files on both algorithms will be measured using the parameters Ratio Of Compression, Compression Ratio, Redundancy, Space Caving, and Time Compression. the file to be compressed is a video file with MP4 format. Video file compression is a process to remove various redundancies from the bit set in a video file so that the size becomes smaller. In the comparison of the two Huffman algorithms with Rice Code, both have a type of lossless compression algorithm, which is a type of compression that can be decompressed and the results obtained from the comparison of the two algorithms, that the Rice Code algorithm is superior to Huffman.